2023
DOI: 10.1155/2023/8897227
|View full text |Cite
|
Sign up to set email alerts
|

Professional Digital Competence: Definition, Frameworks, Measurement, and Gender Differences: A Systematic Literature Review

Sònia Sánchez-Canut,
Mireia Usart-Rodríguez,
Carme Grimalt-Álvaro
et al.

Abstract: In the current context of increasing digitization, professionals need to be digitally competent. In addition, women’s low participation in the technology field indicates the persistence of a digital gender gap in the economic and social spheres. A key aspect to help reducing digital inequality is the role that the digital competence (DC) plays in the professional development of women, allowing them to enter to a job market still coped by men. The current systematic literature review, following the PRISMA proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Traditionally, a gender gap has been observed in the field of digital competencies [88,89], specifically in the field of journalism. In this regard, it has been observed that women have less presence in digital media and produce less digital content [90], although more recent studies suggest that women identify fake news more frequently than men [91].…”
Section: Mechanisms and Tools To Fight Disinformationmentioning
confidence: 99%
“…Traditionally, a gender gap has been observed in the field of digital competencies [88,89], specifically in the field of journalism. In this regard, it has been observed that women have less presence in digital media and produce less digital content [90], although more recent studies suggest that women identify fake news more frequently than men [91].…”
Section: Mechanisms and Tools To Fight Disinformationmentioning
confidence: 99%